2015
DOI: 10.1111/cch.12289
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of developmental delay among children aged 3–60 months in Izmir, Turkey

Abstract: Identifying developmental delay in children earlier by a validated, reliable, parent-completed questionnaire like Ages and Stages Questionnaires and detecting risk factors for delay are crucial for primary care where their growth and development are monitored. Identifying developmental delay and early referral to rehabilitation services may help improve children's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 31 publications
5
27
3
Order By: Relevance
“…The prevalence of child developmental delay in our study was twice as high as that from studies in Iran and Turkey [9,13]; however, the tool used for measuring the development was different. Both these other studies used the Ages and Stages Questionnaire (ASQ) which asked the parents about children's activities and performances [14,15].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The prevalence of child developmental delay in our study was twice as high as that from studies in Iran and Turkey [9,13]; however, the tool used for measuring the development was different. Both these other studies used the Ages and Stages Questionnaire (ASQ) which asked the parents about children's activities and performances [14,15].…”
Section: Discussioncontrasting
confidence: 66%
“…The prevalence of child developmental delay varies from 5% to 40% depending on the characteristics of the study population and tools used [8][9][10][11][12][13]. Tools for measuring child development should be designed to measure an individual's performance and provide a comparison of standardized norms [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Demirci and colleagues reported that the prevalence of SDD using ASQ-TR during childhood in Turkey was 6.4% in a community-based sample of children aged 3–60 months 12. The relatively low prevalence of SDD in our study compared with other studies may be explained by the wide range of selection criteria used, as we included all children aged 24–60 months (screened by nine questionnaires), excluding children with chromosomal and/or genetic disorders, chronic illness, neurological diseases and those with congenital anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of development delay in any of the five development domains in our study (9.2%) which is in line with existing literature in other settings. (5, 6, 8) In non-population representative samples in Brazil, the prevalence of development delay was reported to range from 21.4% to 46.3%, using different appraisal tools and in different ages. (20, 21) To the best of our knowledge this is the first comprehensive population-based study of the risk of child development delay in Brazil.…”
Section: Discussionmentioning
confidence: 99%